ENERGY SECURITY POLICY OF PT. PERTAMINA FACES THE DYNAMICS OF FOREIGN POLICY - Budi Pramono; Lukman Yudho Prakoso; Gabriel Choirul Alman; Rianto Rianto; Yudi Sutrasna; Edy Sulistyadi; Junindra Duha; Haetami Haetami; Arifuddin Uksan; Sri Sundari; Juliana Juliana; Ahmad Ahmad (Jurnal Cakrawala Ilmiah, 2022)
: Indonesia is a country that has diversity abundant natural resources, including energy resources. Indonesia's role in the energy sector is very large, for example Indonesia is one of the exporters of coal and LNG (Liquefied Natural Gas) is the largest in the world. Wealth is real is the capital to become a great country. PT. Pertamina (Persero) as a national-scale oil company that has been committed to providing the best contribution to the Indonesian economy. The research method uses descriptive qualitative. The results of the study show that Kube 1998 includes five main policy and nine policies supporters. The main policies are: Diversification is diversification use of energy, both renewable or non-renewable. Intensification is the search for energy sources through survey and exploration activities so that can upgrade new reserve especially fossil energy. Conservation is carried out starting from the upstream side down to the bottom. The main target of Pertamina's policy related to the protection of biodiversity is ecosystems located in/close to Pertamina's working areas, both on land and in sea. Determination of the average energy price which gradually directed to follow the mechanism market and Paying attention to environmental aspects in development in the energy sector including in it gives priority in utilization of clean energy. The novelty of this research is PT. Pertamina Faces The Dynamics Of Foreign Policy seeks to increase its role in driving the national economy by developing strategies to meet national energy in a sustainable manner and reduce imports of oil and gas